On the empirics of geographic isolation and technology adoption - Kodila-Tedika, Oasis; Duan, Yi; Yemba, Boniface P.; Cinyabuguma, Matthias (Applied economics letters, 2024)
This article examines the impact of prehistoric geographic isolation on technology adoption in both the historical period and contemporary period. The regression results show that geographic isolation tends to have a persistent positive effect on technology adoption, therefore, providing empirical support for the theory that geographic isolation is beneficial for economic development by stimulating innovations and improving technology.